CUSTOMER SATISFACTION WITH FITNES SERVICES AND EQUIPMENT FACILITIES IN GYM ACADEMIC FACULTY OF SCIENCE OF SCIENCE, JAKARTA STATE UNIVERSITY - Sukiri; Iwan Setiawan; Trada Anggah (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to determine the level of customer satisfaction facilities for services and fitness equipment at the Academic Gym, Faculty of Sport Science, State University of Jakarta. The implementation of this research was carried out at Academic Facility, Faculty of Sport Science, State University of Jakarta. The distribution of questionnaires was carried out in June - July 2020 using Google forms and shared through to the WhatsApp Group. The method of this research using survey and descriptive analysis. It means that the data obtained from the results of distributing questionnaires on forms collected according to the indicators are then analyzed and finally presented in a report in descriptive form. The population used in this study were all users of the Academic Fitness equipment who are members of the network and not members. While the sample was determined using cluster random sampling, namely the sampling technique in groups. The data returned by respondents indicates that the average respondent is satisfied with the facilities, facilities and infrastructure included in the physical evidence indicator which almost reaches 85%. For reliability indicators, customers who are satisfied and almost satisfied are almost 100%, namely 97.8%. The level of satisfaction and very satisfying indicators of the responsiveness of officers at the Academic Gym reached 93.5%. The guarantee indicator offered by the Academic Gym also scored quite high, namely 90.7%. Meanwhile, the indicator of empathy is also quite high, reaching 96.4% for the satisfaction level of the attitude of the Academic Gym officers. Finally, the decision to be taken by customers who will be loyal to use the Akademik Gym as a fitness center is only 68.6%, meaning that the possibility of the indicator will switch to another fitness place is 31.4%.